Studying lack of awareness of cognitive decline in neurodegenerative diseases requires measures of both anosognosia and denial - Prigatano, George P.; Russell, Sydney; Meites, Tiffany M. (Frontiers in Aging Neuroscience, 2024)
The cause(s) of lack of awareness of cognitive decline in neurodegenerative diseases can be multifactorial. Yet neurologically oriented research on anosognosia of cognitive decline almost exclusively assumes that the underlying disturbance of neuro-networks that support various cognitive functions accounts for the reduced self-awareness. Cultural and psychosocial factors, including the person’s emotional state, however, can contribute to the underreporting or avoidance of admitting to cognitive impairments in neurodegenerative diseases. Research on the causes of lack of awareness of cognitive decline in neurodegenerative disorders needs to include these variables. We briefly present two case examples of underreporting or “unawareness” of memory difficulties in persons with mild cognitive impairment (MCI) (or minor neurocognitive disorder). One presented with classic anosognosia for memory impairment, while the other initially reported no memory impairment but later admitted to “denying” her memory difficulties secondary to anxiety. Based on these patients’ clinical presentations and available research, we suggest three potential screening items that may help identify probable denial of memory impairments when studying anosognosia in MCI.